Peran Kepemimpinan dalam Meningkatkan Kinerja Organisasi PBB Dipangkalpinang: Penelitian - Anggun Sidabutar; Adriyan Maulana Harahap; Nur Sawliyah Nasution; Widya Clara Purba (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the role of leadership in improving the performance of the Pemuda Batak Bersatu (PBB) organization in Pangkal Pinang. Leadership in community organizations plays a crucial role as a driver, guide, and role model for its members. The research employed a descriptive qualitative method with data collection techniques including interviews, observations, and documentation involving PBB leaders and members. The findings reveal that an open, democratic leadership style with effective communication significantly contributes to enhancing member participation, internal cohesion, and the successful implementation of the organization’s social and cultural programs. Leadership has also been shown to strengthen the identity and solidarity of the Batak community within Pangkal Pinang’s multicultural society. Thus, adaptive leadership that emphasizes shared values becomes a key factor in sustaining the organization’s existence while simultaneously improving the performance of PBB as a youth forum that contributes positively to its surrounding community.